محمدﷺیامائتری (Maitreya) گوتم بدھ کی پیشین گوئیاں:تحقیقی مطالعہ: Muhammad (PBUH) “Maitreya” In The light Of the Foretelling’s of Gautama Buddha - Ayesha Mustaq; Dr. Muhammad Abdullah (MEI, 2023)
Allah Almighty has sent Prophets in every age for the guidance of human beings. There is no region of the world in which no warner has come. Gautama Buddha (483-563 B.C.) was the world's spiritual leader, although his teachings were largely based on moral values. In his writings, there are various sayings which are about Prophet Muhammad (PBUH). Some names are aseribed to Prophet Muhammad (Peace and Blessing of Allah be upon him). The most important name is Maitreya, which means a person of honor and respect, who will come in later times. When the religion will abolish, then Maitreya Buddha will appear. Buddha Maitreya's birth conditions. Heredity and family traits. Different names of Buddha Maitreya. Owner of great people. Great winner. Bright shiny. Da'i Maitreya. Shaaf (Healing) with cleanliness / purity. Eraser. Revolutionary reformer. Emigrant. In this research article, the authors have tried to trace many attributes of the Prophet Muhammad (PBUH) from the primary literature of Buddhism. This article will have many new aspects; new angles will emerge for other researchers.